Decadent vegan cakes : outstanding plant-based recipes for layer cakes, sheet cakes, cupcakes and more - Roberts, Charlotte (Recipe developer) (Page Street Publishing, 2023)
"Whip Up Bakery-Quality Vegan Cakes Right in Your Own Kitchen. Making delicious plant-based cakes is foolproof thanks to this outstanding collection of recipes from blogger Charlotte Roberts. Ranging from mouthwatering layer cakes perfect for a celebration to tasty loaf cakes that can be ready in no time at all, Charlotte's wide array of bakes have you covered no matter what flavor or style of cake you're in the mood for. Her craveworthy recipes include: • Ultimate Chocolate Fudge Cake • Gingerbread Latte Layer Cake • Lemon Curd & Poppyseed Cake • Apple Crumble Loaf Cake • The Best Vegan Coconut Cake • Chocolate Orange Layer Cake • Strawberry Swirl Cake • Browned-Butter Chai Cupcakes • Carrot Cake Loaf • Pumpkin-Spiced Layer Cake. Bursting with recipes that will bring you back for seconds (and maybe thirds!), as well as all the tips and tricks you need to demystify vegan baking, this will be your go-to guide for vegan cakes for every occasion" --